Material Hardships and Cultural Resilience: The Role of Traditional Practices in Momaday’s ’The Indolent Boys’ and ’Children of the Sun’ - Nadia Anjum; Dr. Zafar Iqbal Bhatti; Khurram Shahzad (Review Journal of Social Psychology & Social Works, 2024)
This study investigates the perpetual association between socialist-style material difficulties according to Marxist literary analysis alongside cultural endurance shown by Raymond Williams in (The Long Revolution 1961) through N. Scott Momaday’s dramatic works The Indolent Boys and Children of the Sun. Traditional cultural practices enable struggling groups and marginalized communities to form identities and recover through cultural adaptations to material changes. Through their parallel explorations of Native American community struggles the plays demonstrate contrasting methods of cultural resilience where The Indolent Boys displays individual responses while Children of the Sun shows community-based approaches to trauma recovery. Through The Indolent Boys viewers explore Native American historical trauma which resulted from economic abandonment and forced cultural assimilation and institutional exploitation that removed children’s cultural and personal integrity. Through his play Children of the Sun Momaday illustrates the Kiowa people’s declining status by showing them suffering from land disintegration alongside resource shortages and disruption of traditional ways of life which put cultural survival at risk. The research demonstrates how cultural traditions enable Native American groups to maintain their cultural identity and create community connections which safeguard Native heritage in ongoing battles for survival.